PELESTARIAN WARISAN BUDAYA CANDI TEGOWANGI MELALUI EDUKASI VISUAL: PEMBUATAN LEAFLET INFORMATIF BAGI MASYARAKAT KEDIRI - Wiratama, Nara Setya; Santosa, Yusuf Budi Prasetya; Setiyonugroho, Ponco; Widiatmoko, Sigit; Ashriana, Khairunisa; Rahma, Sesylia (Universitas Nusantara PGRI Kediri, 2025)
Tegowangi Temple is one of the important relics of the Majapahit Kingdom era, which not only holds historical and architectural value but also has great potential as a medium for local cultural education. However, the low awareness of the surrounding community regarding the importance of preserving this cultural heritage site poses a challenge that needs to be addressed through a contextual and communicative educational approach. This community service activity aims to strengthen the cultural literacy of the community in Tegowangi Village, Plemahan Sub-district, Kediri Regency, through the development of educational leaflets as an attractive and easily accessible medium for socialization. The leaflets are designed with content based on scientific literature and popular historical narratives, containing information about the location, history, and architecture of Tegowangi Temple. The implementation methods include field observations, limited interviews with local figures, literature reviews, the creation of visual content based on participatory graphic design, and the distribution of leaflets to the community and visitors. This activity involved collaboration between faculty members, students, and village officials as active partners. The results of the activity demonstrated that the leaflet played a significant role in enhancing the community's knowledge of local cultural heritage, fostering a sense of ownership toward the historical site, and encouraging community participation in long-term conservation efforts. This program is recommended as a community-based visual education model that can be replicated at other cultural sites using a similar approach.